"It Made Me Want to be that Spark": A Case Study of the Experiences of College Student Group Exercise Instructors. Issue 2 (October 2017) - Buzzelli, Armand
While recent research has focused on leadership and development in collegiate club and intramural sports participants, many of the findings and suggestions may be deemed applicable to student roles within college fitness and group exercise programs. The purpose of this exploratory case study was to learn about the leadership experiences, motivations, benefits, and perceived limitations to group fitness instruction for students at a small, private, Mid-Atlantic university, and to discover potential influences of these experiences on the overall collegiate experience. The researcher was interested in insights of both current and recently graduated students who serve as group fitness instructors at their college. The researcher interviewed eight participants from one institution selected through convenience sampling. While this study used a small sample from one institution, interviewee responses were consistent, relevant, and may be expanded upon in future research. Participants reported that they improved leadership skills, public speaking, conflict resolution, and developed a campus identity as a result of teaching group exercise. The majority of the participants had not considered the benefits of their experiences in terms of professional development, and relationship building before their participation in the study. These findings demonstrate that campus recreation departments need to provide evidence to students and university administration that their programs not only provide enjoyment and health benefits for participants, but also a litany of "soft skills" and professional experiences that employers will look for after graduation.